Formulasi Sediaan Nanoemulsi Antiselulit Mengandung Kafein dan Minyak Biji Anggur (Vitis vinifera L.) - Sani Ega Priani; Dinnanda Yussepina Wulansari; Fitrianti Darusman (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Caffeine is a methylxantin derivative that has anti-cellulite activity by increasing lipolysis. Grape seed oil containing oligoproanthocyanidin which can also act as an anti-cellulite. The nanoemulsion system is known could increase percutaneous penetration of lipophilic or hydrophilic compounds such as caffeine. This study aims to develop caffeine nanoemulsion containing grape seed oil and to determine the effect of nanoemulsion formulation on the percutaneous penetration of caffeine. Nanoemulsion preparations were made using grapeseed oil as the oil phase, tween 80 as a surfactant, glycerin as a cosurfactant, with various concentration of caffeine as the active substance (1;1,5;and 2%). The preparations were characterized by organoleptic, homogeneity, pH, viscosity, rheology, spreadability, %transmittance, globule size distribution, and physical stability testings. The percutaneous penetration test was carried out in vitro using franz diffusion cell. The results showed that the nanoemulsion preparation containing 1% caffeine with 5% of grapeseed oil had good physical characteristics with transparent and homogeneous appearance, Newtonian flow properties, percent transmittance value of 99.17 ± 0.06% and globule size of 101 ± 13 nm. Nanoemulsion was able to increase the penetration of caffeine based on in vitro testing compared to the gel dosage form which were statistically significant (p <0.05).